O22. Monte-Carlo commissioning of small irregularly-shaped intra-operative radiotherapy beams. (September 2016) - Lazarus, G.; Hering, E.; du Plessis, F.
Abstract : Introduction: The objective of this study is to validate Monte Carlo (MC) based calculations for small irregularly shaped intra-operative radiotherapy (IORT) electron beams. Treatment is delivered using an electron beam passing through an IORT cone with custom built irregularly-shaped alloy cut-outs. Materials and methods: All measurements were performed on the Siemens Primus LINAC utilising the PTW MP3 therapy beam analyser and PTW pinpoint chamber. Percentage depth dose and profiles at various depths were obtained for the 6 MeV, 12 MeV and 18 MeV electron beams with the standard 10 × 10 cm 2 and 5 cm circle applicators for MC commissioning purposes. Identical measurements were done with the IORT cones of diameters 19 mm, 45 mm and 64 mm with and without irregularly-shaped alloy cut-outs. Output factors for all energy/applicator, energy/cone and energy/cut-out combinations were measured. DOSXYZnrc was used to calculate 3D dose distributions in a voxel-based phantom using the individual phase space files (obtained from BEAMnrc simulations) as the source. The data-extraction tools BEAMDP, MCSHOW, Grace, Verisoft and STATDOSE were used to extract and analyse the simulation results. Results: For all the energies investigated, direct comparison between measurement and simulation of Rmax, R90, R80, and R50 yielded differences of less than 1 mm for the standard 10 × 10 cm 2 and 5 cm circle applicators used for MC commissioning. For the IORT cones and cut-outs, maximum differences of 1.5 mm and 1.0 mm respectively were observed for these points. All points that failed the Gamma Index (GI) criteria of 3 mm/3% for profile comparisons were in the high dose gradient regions and/or at the extreme lateral extent of the beam. A maximum difference of 4.04% and 7.82% in cone factor and cut-out factor respectively was observed for the smallest cone and cut-out for 6 MeV. The statistical variance of all MC calculations was below 1%. Conclusion: The MC based dose calculation system evaluated in this study has been successfully validated and is acceptable for clinical implementation.